Calcium-Permeable AMPA Receptors Mediate Timing-Dependent LTP Elicited by Low Repeat Coincident Pre- and Postsynaptic Activity at Schaffer Collateral-CA1 Synapses. (9th September 2021) - Cepeda-Prado, Efrain A; Khodaie, Babak; Quiceno, Gloria D; Beythien, Swantje; Edelmann, Elke; Lessmann, Volkmar
Abstract: High-frequency stimulation induced long-term potentiation (LTP) and low-frequency stimulation induced LTD are considered as cellular models of memory formation. Interestingly, spike timing-dependent plasticity (STDP) can induce equally robust timing-dependent LTP (t-LTP) and t-LTD in response to low frequency repeats of coincident action potential (AP) firing in presynaptic and postsynaptic cells. Commonly, STDP paradigms relying on 25–100 repeats of coincident AP firing are used to elicit t-LTP or t-LTD, but the minimum number of repeats required for successful STDP is barely explored. However, systematic investigation of physiologically relevant low repeat STDP paradigms is of utmost importance to explain learning mechanisms in vivo. Here, we examined low repeat STDP at Schaffer collateral-CA1 synapses by pairing one presynaptic AP with either one postsynaptic AP (1:1 t-LTP), or a burst of 4 APs (1:4 t-LTP) and found 3–6 repeats to be sufficient to elicit t-LTP. 6× 1:1 t-LTP required postsynaptic Ca 2+ influx via NMDARs and L-type VGCCs and was mediated by increased presynaptic glutamate release. In contrast, 1:4 t-LTP depended on postsynaptic metabotropic GluRs and ryanodine receptor signaling and was mediated by postsynaptic insertion of AMPA receptors. Unexpectedly, both 6× t-LTP variants were strictly dependent on activation of postsynaptic Ca 2+ -permeable AMPARs but were differentially regulated by dopamine receptor signaling. Our data show that synaptic changes induced by only 3–6 repeats of mild STDP stimulation occurring in ≤10 s can take place on time scales observed also during single trial learning.